2020
DOI: 10.1038/s41467-020-18491-9
|View full text |Cite
|
Sign up to set email alerts
|

The lysophospholipase D enzyme Gdpd3 is required to maintain chronic myelogenous leukaemia stem cells

Abstract: Although advanced lipidomics technology facilitates quantitation of intracellular lipid components, little is known about the regulation of lipid metabolism in cancer cells. Here, we show that disruption of the Gdpd3 gene encoding a lysophospholipase D enzyme significantly decreased self-renewal capacity in murine chronic myelogenous leukaemia (CML) stem cells in vivo. Sophisticated lipidomics analyses revealed that Gdpd3 deficiency reduced levels of certain lysophosphatidic acids (LPAs) and lipid mediators in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 53 publications
1
33
0
Order By: Relevance
“…Unlike the RNA transcripts, we observed no difference in immunofluorescence intensity between genotypes. GDPD3 has recently been postulated to regulate FOXO3a/β-catenin binding and inhibition of the AKT/mTORC1 pathway via mediation of lysophospholipid metabolism 51 . It is possible that in the absence of FOXO3, residual GDPD3 may alter its LPA production.…”
Section: Resultsmentioning
confidence: 99%
“…Unlike the RNA transcripts, we observed no difference in immunofluorescence intensity between genotypes. GDPD3 has recently been postulated to regulate FOXO3a/β-catenin binding and inhibition of the AKT/mTORC1 pathway via mediation of lysophospholipid metabolism 51 . It is possible that in the absence of FOXO3, residual GDPD3 may alter its LPA production.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, we reported that the lysophospholipid metabolism enzyme Gdpd3 plays a critical role in the maintenance of CML stem cells in vivo [45]. We first conducted RNA-Seq analysis to compare gene expression profiles between murine normal HSCs and CML stem cells, and discovered that the most primitive LT-CML stem cells express Gdpd3 more highly than do normal LT-HSCs.…”
Section: Lysophospholipid Metabolismmentioning
confidence: 99%
“…The question then arises: What is the factor that overcomes BCR–ABL1 and suppresses Akt activation in CML stem cells such that Foxo3a is allowed to function? Our investigation revealed that lysophospholipid metabolism inhibits Akt, and that it is the lysophospholipase D enzyme Glycerophosphodiester Phosphodiesterase Domain Containing 3 (Gdpd3) that plays an essential role in maintaining stem cell quiescence and TKI resistance in CML stem cells [ 14 , 15 ]. This involvement of lysophospholipid metabolism in CML stemness opens up a new field of investigation in the realm of novel CML treatments.…”
Section: Introductionmentioning
confidence: 99%
“…To date, three lysophospholipase D enzymes, namely Autotaxin (ATX), GDPD3 (also termed GDE7) and GDPD1 (GDE4), have been shown to specifically hydrolyze the polar base of lysophospholipids, such as choline, ethanolamine, inositol and serine [ 19 , 20 , 21 ]. Recently, we reported that Gdpd3 plays an essential role in maintaining CML stemness in vivo [ 14 ].…”
Section: Introductionmentioning
confidence: 99%